JURIDICAL REVIEW OF THE FACILITATION OF COMMUNITY PLANTATION DEVELOPMENT BY PLANTATION COMPANIES - Lestariana Marwassari; M. Yamani; Emelia Kontesa (Bengkoelen Justice : Jurnal Ilmu Hukum, 2021)
The government regulates the facilitation of community plantation development as much as 20% of the area of rights by plantation companies. This provision which is the obligation of the company was still not regulated in a clear and firm legal arrangement so that it created multiple interpretations in its application. Based on this matter, the writer was motivated to analyze the legal arrangements for the facilitation of community plantation development by plantation companies and the obstacles encountered in the implementation. The plantation company which was the focus of the research was PT. Pamor Ganda with Business Right (known as HGU in Indonesia abbreviation) Number 16/1989 by studying the HGU extension document. This was a normative research with a statutory approach. The method of analysis performed was content analysis, then the interpretation was carried out to understand the conclusions. The results showed that legal arrangements in the land sector, Micro, Small, Medium Enterprises (MSMEs), and plantations had not been able to solve the problems that exist in the implementation of facilitation of community plantation development by plantation companies. The company's obstacle was that the plasma farmers' plantation area around the companies’ plantation area had not been able to meet the 20% area requirement. While PT. Pamor Ganda had fulfilled its obligation to facilitate community plantation development by releasing its 114 hectare of HGU area.